Case Report: Robotic pylorus-preserving pancreatoduodenectomy for periampullary rhabdomyosarcoma in a 3-year-old patient - Liang, Zijian; Lan, Menglong; Xu, Xiaogang; Liu, Fei; Tao, Boyuan; Wang, Xinxing; Zeng, Jixiao (Frontiers in Surgery, 2024)
Periampullary neoplasm is rare in pediatric patients and has constituted a strict indication for pancreatoduodenectomy, a procedure sporadically reported in the literature among children. Robotic pancreatoduodenectomy has been routinely performed for periampullary neoplasm in periampullary neoplasm but only a few cases in pediatric patients have been reported. Here we report the case of a 3-year-old boy with periampullary rhabdomyosarcoma treated with robotic pylorus preserving pancreatoduodenectomy and share our experience with robotic pancreatoduodenectomy in pediatric patients. A 3-year-old boy presented with obstructive jaundice and a mass in the pancreatic head revealed by imaging. A laparoscopic biopsy was performed. However, jaundice progressed with abdominal pain and elevated alpha-amylase leading to urgent robotic exploration in which a periampullary neoplasm was revealed and pathologically diagnosed as Rhabdomyosarcoma by frozen section examination. After pylorus preserving pancreatoduodenectomy, a conventional jejunal loop was performed following a Child reconstruction including an end-to-end pancreaticojejunostomy, followed by end-toside hepaticojejunostomy and duodenojejunostomy. Delayed gastric emptying presented with increasing drain from the nasogastric tube a week after the surgery and recovered spontaneously within 10 days. In a 13-month follow-up until the present, our case patient recovered well without potentially fatal complications, such as pancreatic fistula. Robotic pancreatoduodenectomy in pediatric patients was efficacious and safe without intra-or post-operative complications.